2023
DOI: 10.4285/kjt.22.0054
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant sequential adrenal and spine metastasis of hepatocellular carcinoma responsive to combined regorafenib and radiotherapy: a case report

Abstract: Adrenal and spinal metastases of hepatocellular carcinoma (HCC) are rare entities with significant morbidity and mortality, particularly after liver transplantation (LT). We report a case of a 49-year-old man who underwent LT for hepatitis B-related end-stage liver disease and HCC (single 4.5 cm lesion [T1N0], without vascular invasion) in 2016. Eighteen months later, adrenal metastasis and hepatitis B seropositive conversion were developed with normal serum tumor. Adrenal metastasis was treated with radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A clinical trial named REGINA aims to evaluate the survival benefits of neoadjuvant regorafenib in combination with nivolumab and short-course RT for stage II and III rectal cancer, the results of which are highly anticipated ( Bregni et al, 2021 ). A previous case showed that a patient with metastatic hepatocellular carcinoma achieved long-term survival of over 71 months after receiving a combination of regorafenib and RT ( Kim et al, 2023 ). RT may improve the tumor microenvironment, promote the release of tumor antigen, and synergistically increase the effects of TKIs and ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial named REGINA aims to evaluate the survival benefits of neoadjuvant regorafenib in combination with nivolumab and short-course RT for stage II and III rectal cancer, the results of which are highly anticipated ( Bregni et al, 2021 ). A previous case showed that a patient with metastatic hepatocellular carcinoma achieved long-term survival of over 71 months after receiving a combination of regorafenib and RT ( Kim et al, 2023 ). RT may improve the tumor microenvironment, promote the release of tumor antigen, and synergistically increase the effects of TKIs and ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, activated carbons are one of the most representative adsorbents with low production costs and properties such as abundant micropores, large surface areas, high adsorption performance, acid/base, and thermal stability [1]. Due to such properties, activated carbons are widely used in diverse liquid-phase and gas-phase processes such as the treatment of heavy metals in wastewater and landfill leachate, CO 2 capture, hydrogen storage, super capacitor and VOCs adsorption [2][3][4]. Since activated carbons are usually made from natural materials such as coconut shells, coal, wood, and petroleum pitch, they are in the form of fine powder or low-stability granules.…”
Section: Introductionmentioning
confidence: 99%